Enhancing Mesh-Based Photoacoustic Tomography with Parallel Computing on Multiprocessor Scheme (Communications in Computational Physics, 2018)
Photoacoustic tomography is an emerging technique in biomedicine that iscapable of visualizing high resolution structural and functional information of tissueup to several centimeters deep. Mesh based numerical reconstruction algorithms havean unrivaled advantage over other reconstruction algorithms in photoacoustic imaging,due to its accurate mathematical modeling and the capability to recover multipleoptical/acoustic parameters in the reconstruction. However, the slow reconstructionspeed and huge memory cost hindered this advanced reconstruction algorithmfrom application areas where large scale reconstruction or real/near-real time reconstructionis required, for example, sub-millimeter or micrometer resolution imaging,photoacoustic guided cancer treatment, etc. In this study, we reported a high performancephotoacoustic tomography method based on parallel computing strategy withmultiprocessor scheme. Our simulation result has shown that the parallelized photoacoustictomography method using multiprocessor scheme is capable of providingfine reconstructed images of blood vessel structures up to 0.14mm in diameter. Furtherphantom experiment demonstrated that cross hairs can be clearly reconstructed,when a mesh comprised of 28512 triangle finite elements is used. Therefore, our multiprocessorbased parallelized photoacoustic tomography might be promising for largescale reconstruction or real/near-real time reconstruction in biomedical application ofmesh-based photoacoustic tomography algorithm.
Keywords: Photoacoustic tomography; finite element method; parallel computing.